Obtaining phenolic extracts from the leaf of Moringa oleifera Lam by using different extraction methods - Claudia Linares Rivero; Janet Quiñones-Gálvez; Aurora Terylene Pérez Martínez; Carol Cristina Carvajal Ortiz; Maribel Rivas Paneca; Geeisy Angela Cid Valdéz; Lianny Pérez Gómez; Susett La Rosa González; Yanelis Karina Capdesuñer Ruiz (Biotecnología Vegetal, 2018)
Moringa oleifera Lam. it is one of the best known and widely distributed species in the world. It is considered as one of the most useful trees, with multiple benefits. One of its distinguishing characteristics is that its leaves accumulate high contents of phenolic compounds, which are investigated for their biological properties. The present investigation was developed with the aim to obtain crude ethanolic leaf extracts, with higher extraction yields and phenolic compounds, from M. oleifera by comparing four extraction methods. The influence of extraction by magnetic stirring, static extraction, extraction by Soxhlet and ultrasound-assisted extraction on the yield of crude leaf ethanolic extract and the concentration of phenolic compounds were determined. The phytochemical characterization of the extract was carried out and the chromatographic profile was determined by thin layer chromatography. A yield of 185.89 mg g-1 of dry mass and the highest concentrations of phenols in the extract (24.86 mg g-1 dry mass) were obtained by magnetic stirring. The qualitative chemical characterization of the phenolic extract of M. oleifera proved the presence of volatile coumarins, triterpenes, steroids, flavonoids, tannins and phenolic compounds detected in the phytochemical and phenolic acids analyses, glycosylated flavonoids, essential oils associated with phenols and compounds with pungent and bitter principle in thin layer chromatography. It is concluded that by the extraction method with magnetic stirring for 3 h, crude ethanolic leaf extracts of M. oleifera are obtained with high yields of extraction and concentration of phenolic compounds of varied nature. Keywords: ethanolic extracts, phenols, moringa, yield